Cryopreservation for Germplasm Conservation: Progress Report on Indonesian Elite Mutant Coconut âKopyorâ - Sisunandar, Sisunandar (Proceeding International Conference on Global Resource Conservation, 2013)
Among Indonesian elite materials, the Kopyor mutant is a paramount interest, as it is much sought after by customers for its soft and sweet flesh, and high prices with more than 10 times higher than the one of a normal fresh coconut. However, this mutant cannot be conserved by normal means such as field genebanks or seed genebank. An alternative conservation method would be one that involves a degree of dehydration and then ultra-cold storage (cryopreservation). However, as yet such protocols developed for Kopyor have been untested and no field-growing plants have been produced back from these techniques. The cryopreservation of zygotic embryos was achieved through the following steps viz.: a rapid tissue dehydration step prior to storage and a rapid warming step upon recovery followed by acclimatization to soil-supported growth. The best protocol was one based on an 8-hour rapid dehydration step followed by rapid cooling step, rapid warming step and an optimized in vitro culture technique. Following this protocol almost 20 % of cryopreserved embryo could be returned to normal seedlings growing in soil. Moreover, 23 % of recovered embryos were viable but unable to produce normal plantlets, mostly showed stunted shoot. These results indicate that it is possible to store coconut kopyor germplasm on a long-term basis using cryopreservation approach, even though the production of abnormal seedlings following cryopreservation as has been seen in many recalcitrant species before remains a major challenge for the cryopreservation protocol.Keywords: cryopreservation, Embryo culture, Germplasm conservation, Kopyor, Rapid dehydration